Characterizing health researcher barriers to sharing results with study participants - Pearl A. McElfish; Christopher R. Long; Laura P. James; Aaron J. Scott; Elizabeth Flood-Grady; Kim S. Kimminau; Robert L. Rhyne; Mark R. Burge; Rachel S. Purvis (Journal of Clinical and Translational Science, 2019)
AbstractIntroduction:Research participants want to receive results from studies in which they participate. However, health researchers rarely share the results of their studies beyond scientific publication. Little is known about the barriers researchers face in returning study results to participants.Methods:Using a mixed-methods design, health researchers (N = 414) from more than 40 US universities were asked about barriers to providing results to participants. Respondents were recruited from universities with Clinical and Translational Science Award programs and Prevention Research Centers.Results:Respondents reported the percent of their research where they experienced each of the four barriers to disseminating results to participants: logistical/methodological, financial, systems, and regulatory. A fifth barrier, investigator capacity, emerged from data analysis. Training for research faculty and staff, promotion and tenure incentives, and funding agencies supporting dissemination of results to participants were solutions offered to overcoming barriers.Conclusions:Study findings add to literature on research dissemination by documenting health researchers’ perceived barriers to sharing study results with participants. Implications for policy and practice suggest that additional resources and training could help reduce dissemination barriers and increase the return of results to participants.